Silence and silencing: the case of trafficked women - Haezreena Begum Abdul Hamid, (Penerbit Universiti Kebangsaan Malaysia, 2019)
This article builds on the agency theory and provides an analysis on how silence has been used as a tool to control trafficked women. The article argues that in many instances, traffickers and state institutions control women by dismissing their voice, or by depriving them from exercising their agency. In this respect, women who are vocal and verbalise their opinions are categorised as defiant and need to be controlled. Such beliefs stem from patriarchal influences that have been normalised and are deeply embedded in social structures, cultures, religions and social practices. To affirm these claims, the study conducted semi-structured interviews with 29 trafficked female migrants from seven different nationalities who were detained in a shelter in Kuala Lumpur, Malaysia. The study also interviewed 12 professionals that mainly consist of government officials to understand the implementation of the victim-protection policies. By providing an insight into women’s experiences of sex-trafficking and state ‘protection’, the article discusses how the victim protection policies act to silence women by force. The findings of the study will demonstrate how silencing is used as a strategy to minimise harm and how women are silenced through language barriers. This article adds knowledge to the trafficking and victimization scholarship and expands the notion of silencing so that it can be more understandable and effective across cultures.